PENGARUH TEKNOLOGI BUDIDAYA DAN DOSIS PEMUPUKAN NPK TERHADAP SIFAT KIMIA TANAH DAN PRODUKSI PADI SAWAH (Oryza sativa L.) - Andria Syah Putra Sufardi Fajri (Jurnal Sains Riset, 2017)
The objectives of this research aimed to study effects of cultivation technology and appropriate dosages of NPK on Characteristics of Soil Chemistry and rice product. The experiment was arranged in a factorial split plot design with three replicates. Factor of cultivation technology consisted of four levels, i.e. legowo system cultivating, conventional system cultivating, salibu technology, and ratooning technology. Factor of appropriate dosages of NPK consisted of three levels i.e. 100 kgs ha-1 NPK Phonska, 200 kgs ha-1 NPK Phonska, 300 kgs ha-1 NPK Phonska. The result showed that cultivation technology exerted higgly significant effect on N-total, pH (H2O), KTK, C–organic, weight of 1000 grains, numbers of productive tillers, yields, and exert a significant effect on Kdd. Appropriate dosages of NPK exerted highly significant effects on yields and exerted a significant effect on N-total and numbers of productive tillers. Interaction between cultivation technology and appropriate dosages of NPKshowed highly significant on N-total, numbers of production tillers and yields. The highest yields of rice showed by cultivation technologylegowo system with appropriate dosages of 300 kgs ha-1 NPK Phonska, however based on financial analysis cultivation technology of salibu turned out the best of other cultivation technology since it required minimum cost.